Social Isolation During COVID-19 Pandemic. Perceived Stress and Containment Measures Compliance Among Polish and Italian Residents - Grabowski, Jakub; Stepien, Joanna; Waszak, Przemyslaw; Michalski, Tomasz; Meloni, Roberta; Grabkowska, Maja; Macul, Aleksandra; Rojek, Jakub; Lorettu, Liliana; Sagan, Iwona; Bidzan, Leszek (Frontiers in Psychology, 2021)
Background. In our study we analyze the association of social isolation in the first phase of pandemic with perceived stress among residents of Poland and Italy with a look on how these populations adjust and comply to implemented regulations, guidelines and restrictions. Materials and Methods. Internet survey with Perceived Stress Scale (PSS-10) and questions regarding mobility patterns, attitude and propensity to adjust towards the implemented measures and current health condition was distributed among Polish and Italian residents (Cronbach’s alpha 0.86 and 0.79 respectively). The sample size was 7108 (6169 completed questionnaires in Poland and 939 in Italy). Results. Polish group had higher stress level than the Italian (mean PSS-10 total score 22,14 vs. 17,01 respectively; p < 0,01). There was a greater prevalence of chronic diseases among Polish respondents. Italians expressed more concern about their health, as well as about their future employment. Italian subjects did not comply to suggested restrictions as much as Poles and were less eager to restrain from their usual activities (social, physical, religious), which were more often perceived as ‘most needed matters’ in Italian than Polish residents. Conclusions. Higher activity level was found to be correlated with lower perceived stress, but the causality is unclear. Difference in adherence to restrictions between Polish and Italian residents suggests that introducing the similar lockdown policies world-wide may not be as beneficial as expected. However, due to the applied method of convenience sampling and uneven study groups one should be careful with generalizing these results.